The Effect of Audit Delay on Stock Price (Study On Companies Listed on The Indonesia Stock Exchange for the 2020 And 2021 Period) - Deden Arifin; Neng Meli (Westscience Press, 2023)
The purpose of this research is to test whether there is an effect of audit delay on stock prices. The theory used in this study is to use the agency theory which in this study is to enter into agreements involving two or more people who have their respective interests. Then the data obtained was from the Indonesia Stock Exchange (IDX) with a sample of 156 companies that experienced audit delays in the 2020 and 2021 periods and were obtained using the purposive sampling method, the analytical technique used in this study is the panel data regression analysis method (pooled data) and get the result that the variable audit delay has no effect on stock prices.